Characterization of cerebro-vascular disease in the Intermediate Care Unit. Multicentre study in the central part of Cuba. - Alba Enseñat Alvarez; Rubén Bembibre Taboada; Maribel Misas Menéndez; Julio Cortizo Hernández; Niurka Galende Hernández; Aleida Hernández Lara; Ramón Erice Lafont (Medisur)
Fundament: Cerebrovascular diseasets constitute the third cause of death and the first cause of disability worldwide and in Cuba, hence it has been included among the prioritised programs of the World Health Organisation and by our Ministry of Public Health. Objective: To characterize cerebrovascular diseasets in the Polivalent Therapy Service of the central region of the country. Method: multicenter descriptive study of a series of cases carried out at the Clinical Surgical Hospitals ¨Dr. Gustavo Aldereguía Lima¨ from Cienfuegos province, and ¨Arnaldo Milián Castro¨ from Villa Clara with a revision of 1218 clinical records of patients who were interviewed and whose data was processed afterwards. Results: There was a predominance of the white race ( 75,3 %), male sex (56,7 %) and hypertension was the risk marker ( 71,3 % ). The isquemic cerebrovascular desease was the most frequent reported with 86,7 % and anti-aggregate platelets was the medication most frequently used (77,5 %) In regards to the location of the lesion 51,1 % were reported in the parietal region and the predominant diagnosis was the atherothrombotic infarct ( 59,9 %). The most common complication was cerebral oedema ( 45,2%) . On discharge the state was ¨alive with disability¨ ( 62,2%). Conclusions: Cerebrovascular diseases is a health problem in our environment. Hypertension is the most frequent risk marker observed and there is a predominance of ischemic ictus . Once established the disease is established, it evolves to disabilities or death in most of the cases.